د ا را رسة أولية عن وبائية داء الالابواغ الخبيئة في أطفال بعض مناطق وادي الشاطيء - Saleh, Mohammed Thabet (The Iraqi Journal of Veterinary Medicine, 2006)
The aim of this study to detect Cryptospordiosis among children (1 day –10 years) in some Wadi Al-Shati areas (Brack ,Akar,Al-Qurda and Wanzreek). A total of 280 faecal samples were examined by flotation with sheather s’ sugar solution and acid fast staining techniques to detect Cryptospordium oocysts .The results of study demonstrated that 29 samples (10 .3 % ) were positive with highest infection rates in young children between ( days and 1-2 years, which reached 34.2 % and 23 % respectively.